Professional Teacher Performance Review - Kusmawati, Wiwik; Kurniawan, Choirul; Zaini, Moh.; Sudarsono, Sudarsono; Ernata, Yusvidha; Irawan, Dedy (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
Aspects Tested in the Teaching Profession, according to Law of the Republic of Indonesia Number 14 of 2005 concerning Teachers and Lecturers Chapter IV Article 8 article 13 (in Komara, 2007) that in the teaching profession several aspects will be tested, including academic qualifications, competence, health physically and spiritually and have the ability to realize national education goals. Competence is knowledge, skills, and abilities or capabilities possessed by a person that have become part of him or herself so that they color their cognitive, affective and psychomotor behavior. This research aims to determine the professionalism performance of teachers. The method used in this research is a literature review study. It can be concluded that teacher performance is not fully supported by an adequate degree of competency mastery.